Online studying instructional measures at the International Relations Department of the National University of Ostroh Academy - Avhustiuk, Mariia; Tymeichuk, Iryna; Konopka, Natalia; Sakhniuk, Oksana; Balashov, Eduard (Journal of Education Culture and Society, 2021)
Aim. The paper’s aim is to present some current specific online studying instructional measures at the International Relations Department of the National University of Ostroh Academy in Ukraine. Methods. The study is devoted to the observation of some theoretical and methodological aspects of the peculiarities of online studying measures at the International Relations Department. The theoretical and comparative methods of analysing the peculiarities of online studying have been taken into account. In order to summarise the current online studying experiences at the International Relations Department, some specific instructional measures for both students and teachers are presented, for example: how to handle the lack of interaction, master self-learning, promote self-regulation strategies and become more strategic thinkers.. The necessity of studying the above-mentioned aspects has been caused by their impact on students’ learning activity, especially in the times of COVID-19 pandemic. Results and conclusions. The focal point of this research is to provide an insight into the background of online studying peculiarities through the prism of Ukrainian teachers and students. The analysis is focused on online studying of foreign languages, as well as the possible online teaching methods of professional disciplines (History of International Relations; Foreign Policy of the Countries of Asia, Africa, and Latin America; International Conflicts; Current Problems of International Relations in the Middle East) at the International Relations Department. What is more, the authors outline how to help students deal with the lack of interaction, master self-learning, promote self-regulation strategies and become more strategic thinkers. The authors also highlight possible challenges for the faculty and suggest ways to overcome those difficulties. Moreover, some major prerequisites of students’ self-regulatory online learning are described. Contribution. The results of the study are instrumental in mastering the peculiarities of online studying through the prism of learning at the International Relations Department of the National University of Ostroh Academy (Ukraine). The findings of this study may be considered important and contribute to future research.